Pengembangan Multimedia Interaktif Kimia Berbasis PBL (Problem Based Learning) untuk Meningkatkan Keterampilan Generik Sains Siswa - Ratna Azizah Mashami; Khaeruman Khaeruman (Hydrogen: Jurnal Kependidikan Kimia, 2020)
Most of the students had difficultyin understanding the concept of chemistry  which is abstract and cannot connect the concepts studied with the phenomena in everyday life.This is because the instructional media and learning models used by the teacher do not pay attention to submicroscopic representations and do not link chemistry with the environment around students.This study aims to develop Chemical Interactive Multimedia (CIM) based on PBL (Problem Based Learning) to improve students' Generic Science Skills (GSS). PBL-based CIM was developed on the concept of salt hydrolysis in a tutorial format. This study was a Research and Development using the ADDIE design. The research procedure consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. The PBL-based CIM effectiveness test against the GSS of MA Darul Habibi NW Paok Tawah students was carried out at the implementation stage using a one-group pretest-posttest design. The instrument used was in the form of a questionnaire to obtain eligibility data and student responses, as well as a description test to obtain KGS data. CIM based on PBL feasibility data will be analyzed using a five-scale absolute norm, student responses were analyzed descriptively, and GSS data were analyzed using a normalized gain score (N-gain). The validation results show that PBL-based MIK has an average score of 92% which means it was very feasible.The limited trial of 12 students stated that PBL-based CIM met the aspects of appearance, readability, language, and ease of use very well.The results of PBL-based CIM trials in learning can increase students' GSS which is indicated by an average N-gain score of 58% in the moderate category.Therefore, it can be concluded that PBL-based MIK was successfully developed in the very feasible category and could improve students' GSS.